2002
DOI: 10.1073/pnas.062041299
|View full text |Cite
|
Sign up to set email alerts
|

Social intelligence, innovation, and enhanced brain size in primates

Abstract: Despite considerable current interest in the evolution of intelligence, the intuitively appealing notion that brain volume and ''intelligence'' are linked remains untested. Here, we use ecologically relevant measures of cognitive ability, the reported incidence of behavioral innovation, social learning, and tool use, to show that brain size and cognitive capacity are indeed correlated. A comparative analysis of 533 instances of innovation, 445 observations of social learning, and 607 episodes of tool use estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
827
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 993 publications
(883 citation statements)
references
References 58 publications
31
827
3
5
Order By: Relevance
“…However, it is entirely consistent with Reader and Laland's [32] proposal that general behavioral flexibility, not tied to any domain in particular (i.e. content-neutral), is the adaptation underlying cognitive performance in primates.…”
Section: Domain-specific or Domain-general Cognitive Abilities?supporting
confidence: 73%
See 2 more Smart Citations
“…However, it is entirely consistent with Reader and Laland's [32] proposal that general behavioral flexibility, not tied to any domain in particular (i.e. content-neutral), is the adaptation underlying cognitive performance in primates.…”
Section: Domain-specific or Domain-general Cognitive Abilities?supporting
confidence: 73%
“…Across primate species, comparative studies have found that the performance of individual species on different cognitive tasks, involving aspects of spatial, physical and social cognition, is highly correlated [25,26,32,80], suggesting the presence of a general factor underlying this variation. They have also found that this general cognitive performance is correlated quite strongly with brain size, corrected slightly for the effects of body size [25,26].…”
Section: Box 2 General Intelligence In Nonhumansmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not interpret this as necessarily implying that there is an evolutionary tradeoff in social and asocial learning capabilities. To the contrary, the observed propensity for social learning and behavioural innovation (which is largely asocial learning) covaries strongly across non-human primates (Reader and Laland (2002)), and we expect this finding to apply generally. Rather, we interpret our findings as indicating regions of the parameter space in which reliance on social or asocial learning rules will differ in their utility.…”
Section: Discussionmentioning
confidence: 84%
“…Various lines of evidence suggest that brain size in primates is both Primate endocranial volumes 3 correlated with cognitive abilities (Reader and Laland, 2002;Deaner et al, 2007) and influenced by a variety of social, ecological, and physiological variables (Clutton-Brock and Harvey, 1980;Byrne and Whiten, 1988;Sawaguchi, 1990;Aiello and Wheeler, 1995;Martin, 1996). The scaling relationship between brain size and body mass in primates (and mammals generally) has also been a major topic of debate, in part because the influence of body mass must be considered in comparative analyses of brain evolution (e.g.…”
Section: Introductionmentioning
confidence: 99%